HISTORICAL INFORMATION ABOUT EXTREME ISSUES - S. T. Qasimova (Galaxy International Interdisciplinary Research Journal, 2024)
In life, a person is always faced with the responsibility of making the most optimal decision regarding a certain problem. Such problems range from economics to technology. In such situations, in most cases, turning to mathematics is the best solution to the problem.